What Makes a “Distinguished Global Scholar” in Global Education? (Trans)formative Experiences Towards Global Mindedness - Tang, Haoming; Tarc, Paul; Budrow, James; Persad, Polin (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2024)
Having an international experience, often through study abroad, has been a consistent theme in global education. There are a multitude of research studies on how international experiences foster global mindedness. In these studies, it is common for researchers to ask participants to reflect on their international experiences. In contrast, we took an alternative and slightly experimental qualitative approach to dig into the processes of becoming globally minded. Using existing and documented narratives as data, we examined the life-long learning processes of 13 “distinguished global scholars.” Our study illuminates the (trans)formative experiences that contributed to their global mindedness. Four common themes emerged from our analysis: (1) experiencing war and/or political tension; (2) encountering social injustice; (3) engaging with sociocultural difference; and (4) leaving the familiar/reaching out to the unknown. The findings and discussion deepen the understanding of how global mindedness is developed and offer insights for educational.